Debatable Topics in PCOS Patients - Kumar Agrawal, Neeraj; Singh, Kiran (IntechOpen, 2018)
The book deliberates a wide range of the latest research issues on polycystic ovary syndrome (PCOS). The topics discussed include the diagnosis and management of PCOS, dwelling in more depth into the pathophysiology of the syndrome and its genetic and epigenetic basis. The book covers a contemplative discussion on the influence of changing lifestyle patterns on PCOS. The book also includes a number of chapters defining a detailed description of the associated morbidities of PCOS and its long-term sequelae. Since PCOS is quite prevalent globally, the book is also of great interest to the public. Providing detailed information suitable for patients and clinicians, it provides information about the various treatment regimens and screening recommendations for women having this condition.